PELAKSANAAN PERJANJIAN JUAL BELI ONLINE (E-COMMERCE) PADA ONLINE SHOP MONSTREATION - Rahmayani Indrasari; Firdaus Firdaus; Ulfia Hasanah (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2018)
Online buying and selling deals are pecianities that bind the need to spend the same amount ofgoods, and other parties acting as buyers tie in to buy something prices and transactions are made using theinternet network. Online shop Monstreation has unique products and jackets in the clothing business offeredon social media. One of them is Instagram. Surely an online shop has several provisions that must be obeyedby the parties so that no loss occurs. Becase of its virtual nature that allows the parties not to face eachother, there will be several disputes.This type of of research is sociological legal research, namely research in the form of empiricalstudies to find theories about the process and the process of working the law in society. In this case theauthor serves the implementation of an online sale and purchase greement (E-commerce). This researchwas conducted at the Monstreation Online shop in the city of Pekanbaru. The population and sampe areonline shop Monstretation and the sampe is buyer at the online shop Monstreation.From the results of the study the authors concluded that the implementation of an online buying andselling agreement (E-commerce) between online shop Monstreation and buyers has not been carried outproperly, this is seen from: First, Default made by Monstreation online shop such as: production defects,late production and shipping of goods. Second: defaults from other buyers, namely: transactioncancellation, asking for compensation that incriminates the online shop. The author's suggestion, First, forthe online shop Monstreation to provide clearer information about products and improve the productionprocess of clothes and jackets, while for buyers to do not cancel the orders, for parties to obey their rightsand obligations. each party well. Second, in a relationship there needs to be good communication betweenonline buying and selling agreements, it is necessary for the parties to establish good communication so thatthe agreement is implemented according to the expectations of the parties so that disputes in theimplementation of online buying and selling can be overcome.Keywords: Buying and selling agreement - Online Shop Monstreation - Default